Activated Human Hageman Factor (XII)* - Speer, R. J; Ridgway, Helen; Hill, J. M (Thrombosis and Haemostasis, 1965)
An improved method for the isolation of highly purified active human Hageman factor has been described. An overall recovery of 25% with a purification of 106 has been achieved. Certain of the physical and chemical characteristics of XII have been elucidated. Selective chemical modification of functional groups and a variety of enzymatic assays have been employed in an effort to shed light on the mechanism of action of this procoagulant.